Pengaruh Pembelajaran Kewirausahaan Terhadap Keterampilan dan Minat Wirausaha Pada Siswa - Danang Prio Utomo (Educatio, 2017)
This study aims to (1) To determine the effect of Learning Entrepreneurship Against Skills And Interests Entrepreneurial Students (2) To determine whether there Effect of Learning Entrepreneurship Against Skills And Interests Entrepreneurial Students (3) To know the effect of Entrepreneurship Learning Skills And Interests Of Entrepreneurial Students. This research was ex-post facto. The research object is a class XI student with the number of samples taken as many as 20 people by random sampling technique. Data collection techniques used were questionnaires, observation, documentation. Data analysis technique used is the prerequisite test, statistical tests, and test hypotheses with a simple analysis and ujit t. From the T test results can be seen from the One-sample test, namely: testing of entrepreneurial learning variable (X) on entrepreneurial skills, from the calculation of t 34.33 2,086 or sig (0.00 0.05. Thus Ha accepted and Ho titolak. for entrepreneurial learning variable (X) of the entrepreneurial Interests (Y2), from the calculation of t 33.56 2,086 or sig (0.00 0.05. thus Ha Ho accepted and titolak. Based on data analysis concluded that there Effect Against Enterprise Learning Entrepreneurial Skills And Interests.